Strengthening the Principle of Al-Adl in Economic Dispute Resolution to Reduce Non-Performing Financing at PT BPR Syariah Dana Monet Palopo Branch - Sukri Wahid; Mujahidin; Muh. Rasbi (LP2M IAIN Palopo, 2025)
This study aims to determine the strengthening of the Al-adl principle in the resolution of economic disputes in reducing non-performing financing at PT. BPRS Dana Monetary Branch Palopo. The research method used is qualitative which analyzes data from arguments, or respondents' answers related to the object of study. The research approach used a case study on several cases of sharia economic disputes that occurred between customers and PT. BPR Syariah Dana Monetary Branch Palopo. The number of respondents was taken from 3 debtors who fell into the default category. Data collection was carried out through interviews, observation, and documentation. Data analysis with the steps of data reduction, data display, and drawing conclusions. This study found that the resolution of sharia economic disputes at PT BPR Syariah Dana Monetary Branch Palopo was carried out through internal mediation and litigation, adjusted to the debtor's condition. Debtors experiencing business decline were given restructuring, while bankrupt ones were given leniency up to voluntary liquidation. For debtors with indications of moral hazard, the bank takes legal action to uphold justice, including the execution of collateral according to court decisions. Strengthening the Al-Adl principle in dispute resolution at PT BPRS Dana Monetary Palopo Branch is carried out through four main steps: a fair approach tailored to the debtor's circumstances, transparency in the resolution process, deliberation for the mutual benefit, and ongoing evaluation to prevent recurrence of disputes.